Results of the cancer screening program in urban areas in Shaanxi province of China, 2019-2020 - Chen, Y; Song, B H; Li, G; Chen, P; Huang, S P; Liao, Z J; Xu, R; Li, Y R (Zhōnghuá zhŏngliú zázhì, 2024)
Analyze the cancer screening status of the cancer screening program in urban areas in Shaanxi province in 2019-2020. The early diagnosis and early treatment project for urban cancers carried out high-risk population screening for 5 types of high-incidence malignant tumors (breast cancer, lung cancer, upper gastrointestinal cancer, liver cancer, and colorectal cancer) in urban areas. Three prefecture-level cities in Shaanxi province with a population of over 1 million (Xi'an, Baoji, and Shangluo) were selected, and 4 communities with a relatively good working foundation were selected in each city. The general population aged 45-74 years was surveyed on the principles of informed consent and voluntariness, and high-risk groups identified through the questionnaire were further subjected to free endoscopy, ultrasound, CT, and other clinical screenings. The high-risk rates, screening compliance rates, and positive detection rates of the above 5 types of malignant tumors were analyzed. A total of 19 632 people comp